EPID-09. QUANTIFYING SOCIAL DETERMINANTS OF HEALTH AMONG GLIOMA PATIENTS. (9th November 2020) - Hutchinson, Angelica; Marshall, Alexandria; Hsu, Fang-Chi; Weaver, Kathryn; DeTroye, Alisha; Houston, Kristin Strickland; Carter, Annette; Chan, Michael; Cramer, Christina; Laxton, Adrian; Tatter, Stephen; Lesser, Glenn; et al.
Abstract: BACKGROUND: Social determinants of health (SDH) are modifiable factors that contribute to health outcomes. Despite studies linking SDHs with cervical, ovarian, and prostate cancer outcomes, few studies have explored SDHs in glioma patients. We conducted a cross-sectional survey to characterize and contextualize SDHs in glioma patients by community income, rural/urban residence, and treatment status. METHODS: Two validated instruments: PRAPARE (Protocol for responding to and assessing patents' assets risks and experiences) and AHC (accountable health communities instrument) quantified SDHs; along with study-specific supplemental questions. Risk scores were calculated and combined into an overall and domain-specific (economic, education, neighborhood environment, social context, and healthcare) SDH risk, with a higher score being indicative of higher SDH risk. Scores were compared between low-income (LIC) vs high-income (HIC) communities (defined by median household income), urban vs rural (defined by zip code), and active treatment vs surveillance (determined by patient medical record) using Wilcoxon rank-sum test. RESULTS: 100 glioma patients were enrolled: mean age 53 years (range: 22–78); 49% male; 18% oligodendroglioma, 34% diffuse astrocytoma, 38% glioblastoma, 10% other glioma; 68% resided in LICs, 27% in rural zip codes, and 51% were on active treatment. Overall, SDH risk scores were low (mean= 4.43-out-of-38). Scores in the healthcare domain were the highest. Compared to patients from LICs, patients from HICs had higher healthcare risk scores (p< 0.05). Surveillance patients had higher overall SDH risk on the AHC than patients in active treatment (p< 0.05), with age being a confounder. In multivariable analysis, younger age, and astrocytoma histology were associated with higher social health risk. CONCLUSION: Glioma patients report relatively few SDH risk factors on standardized instruments designed for general clinic populations. The higher health risk observed in patients in HICs and higher AHC risk for those in surveillance will be further explored in planned qualitative analysis.